A Statin a Day to Keep the Doctor Away? Comparing Aspirin and Statins for Primary Prevention of Cardiovascular Disease. (September 2014) - Dietrich, Eric; Davis, Kyle
For the primary prevention of cardiovascular (CV) disease, aspirin reduces the risk for major vascular events by approximately 15% to 20% with an absolute reduction of approximately 0.1%. Major bleeding occurs at an excess of approximately 2 cases per 1000 patient-years with aspirin therapy. For primary prevention, statin therapy has been shown to reduce the risk of CV events by approximately 30% to 40% with an absolute reduction of 1% to 2%. Rhabdomyolysis is rare, with an incidence of 3.4 cases per 100 000 patient-years. Compared with aspirin, statins have a more favorable risk-to-benefit profile for primary prevention.